Peran Penetapan Harga Menu dalam Meningkatkan Daya Tarik Wisata Kuliner: Studi Kualitatif pada UMKM Kuliner di Johor Bahru, Malaysia - Marisa Nainggolan; Rika Yuanti; Linda Rosiyanti; Suhandi, Suhandi; Diah Marga Retha; Mutia Setia Nengbudi; Mhd. Taufiq Raka Saputra; Rony Agustiadi; Oktavianti, Oktavianti; Tibrani, Tibrani; Cen Sui Lan (Lembaga Teewan Journal Solutions, 2026)
Culinary tourism has become one of the main attractions that contributes to tourism development while creating opportunities for micro, small, and medium-sized enterprises to improve their competitiveness. In this context, menu pricing is not only a business strategy but also influences tourists’ perceptions in choosing culinary destinations. This study aims to analyze the role of menu pricing in enhancing the attractiveness of culinary tourism among micro, small, and medium-sized culinary enterprises in Johor Bahru, Malaysia. A descriptive qualitative approach was employed. Data were collected through observations, interviews, documentation, and secondary sources, and analyzed using data reduction, data display, and conclusion drawing. The findings reveal that menu pricing aligned with tourists’ purchasing power and preferences increases visit intention and strengthens business competitiveness. Competitive prices, supported by product quality, service, and authentic local menus, also create positive culinary experiences that encourage tourist satisfaction and revisit intention. These findings indicate that menu pricing plays an important role in supporting sustainable culinary tourism development while strengthening the contribution of micro, small, and medium-sized enterprises to the tourism sector in Johor Bahru, Malaysia.